Tema liceale (1): Non si dee l’uomo contentare di fare le cose buone - Gramsci, Antonio (International Gramsci Journal, 2024)
This is the Italian version of Gramsci’s essay based on the phrase “Non si dee l’uomo contentare di fare cose buone” from the sixteenth century author Giovanni Della Casa’s Galateo. This starting point leads into a discussion of aesthetics, art and beauty and their accessibility to the different classes and strata of society. Only in galleries and museums, the preserve of the “initiated”, were art forms accessible. The lower strata of society adopted forms of adornment and decoration which, although aesthetically ugly, in a primitive way showed the yearning for beauty. The styles needed channelling to realize beauty; the nascent garden cities in England indicated what could be achieved while, in contrast to the luxurious mansions of the rich in Italy, or even the aesthetic content typifying ancient Greece and Rome, the working people were confined to fetid alleyways and squalid housing, showing up in the stress of modern life: for the Aristotelian catharsis to come about the artistic spirit must predominate.